1997
DOI: 10.1021/np9606761
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Determination of Sulfonoquinovosyl Dipalmitoyl Glyceride, a P-Selectin Receptor Inhibitor from the Alga Dictyochloris fragrans

Abstract: Bioassay-guided fractionation of the marine alga Dictyochloris fragrans led to the isolation and identification of sulfonoquinovosyl dipalmitoyl glyceride (1). The structure of 1 was determined by a combination of spectroscopic methods. On the basis of P-selectin inhibition assays (i.e., P-selectin-IgG ELISA, cell binding assay of receptor globulin, and platelet:HL60 adhesion, it was demonstrated that 1 selectively blocks the P-selectin-ligand interaction in vitro and could be considered a lead compound for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…12) On the other hand, it was reported that sulfolipids also possess distinct physiological functions. [13][14][15][16] It is also well-known that lysolecithin has a hemolytic effect in vitro that increases the permeability of the lipid bilayer, leading to easy incorporation of this molecule, as well as surfactant, into the membrane. [17][18][19] Sugiyama et al reported that lysosphingolipid had strong hemolytic activity as compared to the corresponding sphingolipid.…”
Section: Discussionmentioning
confidence: 99%
“…12) On the other hand, it was reported that sulfolipids also possess distinct physiological functions. [13][14][15][16] It is also well-known that lysolecithin has a hemolytic effect in vitro that increases the permeability of the lipid bilayer, leading to easy incorporation of this molecule, as well as surfactant, into the membrane. [17][18][19] Sugiyama et al reported that lysosphingolipid had strong hemolytic activity as compared to the corresponding sphingolipid.…”
Section: Discussionmentioning
confidence: 99%
“…1. In our previous studies, an SQDG from algae or pteridophytes were mammalian DNA polymerase ␣, ␤ and TdT specific inhibitors (1-3), and several SQMG/SQDG from natural products were found as bioactive compounds (13,14 (4). The chemical structures of the sea urchin SQMG and cyanobacterial SQDG were different from each other.…”
Section: Resultsmentioning
confidence: 99%
“…Each fraction was tested for anti HSV-1 activity. 1 H, 13 C, 1 H-1 H COSY, NOESY, HMQC, and HMBC experiments were carried out on a Bruker DRX operating at 400 MHz for protons and 100 MHz for carbon. The solvent for NMR spectra was deuterated chloroform (CDCl 3 ).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…It is located in thylakoid membranes where it appears to be involved in maintaining a constant ratio of anionic lipids. Besides its role in the thylakoid membrane, SQDG is an attractive compound for development of new drugs because of its extensive biological activities which include inhibitory effects on DNA polymerase and HIV-reverse transcriptase, P-selectin receptors, the AIDS virus, telomerase, and inflammation/proliferation [11][12][13][14][15][16] . Cyanobacterium, Spirulina platensis, is a rich source of valuable compounds such as the antioxidant phycocyanin and polyunsaturated fatty acids (linoleic acid and gamma-linolenic acid) which have an important role in human metabolic pathways, particularly as a precursor of one kind of prostaglandin 17,18 .…”
Section: Introductionmentioning
confidence: 99%